Purge and trap system (P&T) with gas chromatograph to analysed methane and nitrous oxide - Stefan Otto; Gregor Rehder (PANGAEA, 2021)
Purge and trap system (P&T) with gas chromatograph to analysed methane and nitrous oxide. The in-house designed purge and trap system (P&T) determines methane (CH4) and nitrous oxide (N2O) concentrations in seawater samples by dynamic headspace method. After desorption of volatile compounds with an inert ultrahigh purity carrier gas (Helium 99.999 % and additional preparation by purifier – VICI – Valco Instruments Co. Inc.), the gases were analyzed by a gas chromatograph (GC) (Agilent 7890B), equipped with a flame ionization detector (FID) for CH4 measurements and an electron capture detector (ECD) for N2O measurements. The analytical system consists of four main components: Firstly, the purge chamber (200 x 24 mm), with integrated frit (porosity 2, Erich Eydam KG, Kiel, Germany) to purge the seawater with helium to displaced dissolved gases. Secondly, the trap (stainless steel, 700 mm x 1/8”, U-shaped), filled with HayeSep D (60/80 mesh, CS Chromatographie Service GmbH, Langerwehe, Germany) to enrich the relevant gas compounds. Thirdly, a connected calibration sampling loop for incorporate gas standards. Finally, the GC, which is connected via 10-port-2-pos valve, is used to separate CH4 and N2O with a special column circuit and a Deans-Switch unit, which regulates the carrier gas flow to the FID or ECD. The GC is run isothermally at 45 °C with a helium flow of 3 mL min-1 respectively 6 ml min-1 in column 1 and column 2 (Length 10 m or 30 m, HP-PLOT/Q+PT, Diam. 530 μm, film 40 μm). Column one allows the pre-separation and separation of undesirable compounds and through column two a further separation between CH4 and N2O is realized. In the FID-mode (Deans-Switch regulates the carrier gas flow to the FID) CH4 is detected during the first 5.0 minutes. After 5.8 minutes the GC system switches in the ECD-mode via Deans-Switch and N2O is detected (6.3 min total runtime). The FID works at 250 °C and the ECD at 345 °C. The FID uses Helium and ECD uses 10 % carbon dioxide in nitrogen as make up gas (in each case 25 ml/min). To ensure the measurement extquotesingles accuracy, calibration standards are measured daily before and after the actual water samples. The calibration range is chosen, so that the samples are within the limits of the calibration methane (CH4) and nitrous oxide (N2O). The standards follow the same time sequence and pathway as the samples. For CH4 and N2O a standard deviation lowers than 1 % is desirable. After successful calibration, the water samples can be measured. The seawater (poisoned with mercury (II) chloride) is stored at 4 °C in 200 ml glass bottles without a headspace. A 100 ml glass syringe (volume calibrated, Fortuna®, Optina®, Poulten & Graf GmbH, Germany) pulls the seawater sample from the glass bottle without creating air bubbles. Around 10 mL of the sample are pushed out of the syringe over valve three into the purge vessel (filled to 1/5). The exact volume of the sample to be measured is calculated with the help of a caliper. The loaded carrier gas passes through a Nafion drying tube (type: MD-050-24S-2092917-06, Ansyco, Karlsruhe, Germany), removing water residues. Then a helium stream (around 100 mL min) transports the water free gases to the cooling trap, where they are capture and concentrated. After 10 minutes of purge time, the trap is placed in a hot water bath (95 °C) and via 10-port-2-pos valve the gas components travel to the GC. At this point in time, the column system is connected to the FID. Methane has a shorter retention time (5.0 min) than N2O, so it is possible to switch after 5.8 min to the ECD-mode to detect N2O (with a 6.3 min retention time). At the end of the measurement day, standards will be remeasured to determine the drift behaviour of the system. In addition, a blank (purged seawater) can be measured, whereby experience shows that the concentration is zero.